Proceedings of the 5th Seminar on Neural Network Applications in Electrical Engineering. NEUREL 2000 (IEEE Cat. No.00EX287)
DOI: 10.1109/neurel.2000.902404
|View full text |Cite
|
Sign up to set email alerts
|

A fuzzy optimization method for CMOS operational amplifier design

Abstract: The aim of the paper is to present a fuzzy method for the optimization of the CMOS operational amplifier design. Our method uses f u z v sytems or fuzzy sets in all stages involved in the optimization process. In order to reduce the time spent for circuit performance evaluation, we use fuzzy system to model each circuit performance. The optimization problem formulation is accomplished in a flexible manner using fuzzy sets to delne fuzzy optimization objectives. We use qualitative design knowledge to modi& the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Several studies can be found in the literature dealing with the application of fuzzy systems [3,4]. Likewise, Oltean et al [5] studied the application of various types of FISs both for modeling and designing electronic circuits; they proposed the application of a fuzzy optimization method to a CMOS operational amplifier. They employed an adaptive neuro-fuzzy inference system (ANFIS) to tune the initial zero-order Sugeno FIS.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Several studies can be found in the literature dealing with the application of fuzzy systems [3,4]. Likewise, Oltean et al [5] studied the application of various types of FISs both for modeling and designing electronic circuits; they proposed the application of a fuzzy optimization method to a CMOS operational amplifier. They employed an adaptive neuro-fuzzy inference system (ANFIS) to tune the initial zero-order Sugeno FIS.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The information can be used to estimate the optimal values of these parameters by means of an expert system. A fuzzy inference system embedded in an optimization loop is used for this purpose [10]. However, the influence of a number of parameters on the simulation results cannot be predicted precisely.…”
Section: Parameter Identificationmentioning
confidence: 99%
“…It adjusts the parameter values for a given set of GA optimization parameters to give the best possible model response [10]. The block diagram of this inner optimization loop is shown in figure 10.…”
Section: Fuzzy Expert Systemmentioning
confidence: 99%